Implementasi Metode 5S Sebagai Usulan Perbaikan dan Pengembangan Manajemen Operasional dan Area Kerja di CV. Gatsu Jaya Perkasa Abadi - Sylvia, Sylvia (Journal of Industrial Engineering & Management Research, 2020)
This study discusses the improvement and development of work areas using the 5S concept approach (Seiri, Seiton, Seiso, Seiketsu, Shitsuke). Currently the work area in the company is irregular and disorganized, there are no policies and procedures to maintain and create an effective, safe, and comfortable work area. The purpose of this research is to make improvements and create standards and procedures for maintaining work areas and to increase discipline in using work standards and facilities by applying the 5S concept. The research was conducted at CV Gatsu Jaya Perkasa Abadi, located in Medan, North Sumatra. The methods used in this research are observation, interview, audit and literature study related to the discussion of this research. The results of this study indicate that the implementation of 5S is very well applied in the work area so that production and management of the work area run effectively.